TACTILE MAPPING AND THE TEACHING OF GEOGRAPHY: THE ADAPTED GLOBE EXPERIENCE - Flaire Jordao, Barbara Gomes; Reinaldo Gimenes de Sena, Carla Cristina [UNESP] (Univ Federal Roraima, 2015)
Social inclusion is a global tendency that goes back to the 1960s and 1970s. The base is a new paradigm built from the perspective that the society is responsible for providing means to insert the visual impaired individual to it. At the end of 2012, of the 700 million people with some disability, 285 million were visualimpaired in the planet. For the last three decades the government has been trying to stablish school inclusion in Brazil. This work studies in what and how School Geography can contribute to the inclusion of impaired students in the regular school class. To that end, we have presented the results of the group construction of a terrestrial globe adapted to teach the concept of geographical coordinates. This topic has raised issues concerning the visual impaired or low sight student perception when abstract subjects are taught in class. More than the production of an accessible material to the students, the reflections resulting from this research have enabled to look for more than just educational inclusion: the social inclusion as well. Through bibliographical research and the evaluation of ninety students, the use of this terrestrial globe inside the regular class has confirmed that the Tactile Cartography can contribute to the teaching of Geography to every student, thus making possible to accomplish activities in group with success. This teaching process using different materials has become very appealing to students and teachers. The Tactile Cartography must not be confined only inside specialized institutions and/or universities, but it must be a part of the school daily life.